2011
DOI: 10.3354/meps09211
|View full text |Cite
|
Sign up to set email alerts
|

Trophic versus geographic structure in stable isotope signatures of pelagic seabirds breeding in the northeast Atlantic

Abstract: Feeding ecology and geographic location are 2 major factors influencing animal stable isotope signatures, but their relative contributions are poorly understood, which limits the usefulness of stable isotope analysis in the study of animal ecology. To improve our knowledge of the main sources of isotopic variability at sea, we determined δ 15 N and δ 13 C signatures in the first primary feather of adult birds from 11 Procellariiform species (n = 609) across 16 northeast Atlantic localities, from Cape Verde (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 59 publications
4
64
1
Order By: Relevance
“…However, with tuna the isotopic values were assumed to reflect the signature of the capture location, although they may have been in transit (i.e., sampled during migration). We found clear spatial patterns in loggerhead Roscales et al 2011). Latitudinal differences in d 13 C are due to temperature, surface water CO 2 concentrations, and differences in plankton biosynthesis or metabolism (Rubenstein and Hobson 2004).…”
Section: Isoscape Patternsmentioning
confidence: 74%
“…However, with tuna the isotopic values were assumed to reflect the signature of the capture location, although they may have been in transit (i.e., sampled during migration). We found clear spatial patterns in loggerhead Roscales et al 2011). Latitudinal differences in d 13 C are due to temperature, surface water CO 2 concentrations, and differences in plankton biosynthesis or metabolism (Rubenstein and Hobson 2004).…”
Section: Isoscape Patternsmentioning
confidence: 74%
“…Our data suggest that Bugio petrels prefer areas with higher wind speed during pre-laying and incubation but not during chick-provisioning, perhaps because of the associated time and energetic cost if a strong headwind delays the return of the adult to feed the hungry chick. The at-sea area used by Bugio petrels during this stage seems to overlap with the distribution of Zino's petrels Pterodroma madeira from Madeira (Zino et al 2011), Cory's shearwater Calonectris diometea from Desertas (Paiva et al 2010a) and Selvagens (Paiva et al 2010c), and Cape Verde shearwater Calonectris edwardsii from Cape Verde (Roscales et al 2011). The African shelf area along the coast of Mauritania appears to be very important for populations of these 4 seabird species for part or all of the year and also for migrant seabirds from elsewhere, including Sabine's gull Larus sabini (Kopp et al 2011), northern gannet Morus bassanus (Stenhouse et al 2012), great skua Stercorarius skua (Magnusdottir et al 2012) and south polar skua S. maccormicki (Fort et al 2012).…”
Section: Habitat Use During the Breeding Stagementioning
confidence: 99%
“…1) is located in the vicinity of the Sub-Polar Front, where cool and productive sub-Artic waters mix with warmer and less productive regimes of the central North Atlantic (Søiland et al 2008). Research has just recently revealed the importance of this area as a hotspot of seabird biodiversity, with several seabird taxa foraging there during different phases of their annual cycle: Some species use this area as their main wintering ground (Sooty shearwaters Puffinus griseus: Hedd et al 2012; black-legged kittiwakes Rissa tridactyla: González-Solís et al 2011, Frederiksen et Roscales et al 2011. Comparatively, Chatham petrels Pterodroma axillaris from the Pacific Ocean also relied on frontal regimes to forage during the pre-laying and incubation periods (Rayner et al 2012).…”
Section: Habitat Use During the Breeding Stagementioning
confidence: 99%
“…Similarly, ␦ 15 N isoscapes have also been ground-truthed for tropical Pacific tunas . However, some large oceanic areas, such as the northeast temperate Atlantic, may not exhibit such isotopic gradients (Roscales et al 2011). All the aforementioned studies determined variation in stable-isotope signatures across the ocean by sampling the relevant species and tissues throughout several localities, but this is costly and not always feasible.…”
Section: ; Williams and Buck 2010) N Uses Of Tracers In Spatial mentioning
confidence: 99%